СИСТЕМА – СТРУКТУРАЛЫҚ ТИЛ БИЛИМИ - Курбаниязов, Г. (SCIENCE and SOCIETY, 2022)
The article analyzes the emergence and formation of system-structural linguistics and its application in Uzbek and Karakalpak language learning.